Adoption Belief Mobile Communication: Konvergensi aktivitas menguatkan Adoption Belief Smartphone, Tablet, dan Handphone - Jandy Luik (Atma Jaya Indonesia Catholic University, Jakarta, 2014)
Decision of using mobile communication device is not a single-independent event, rather it is a series of cognitive understanding. Adopting a model of adoption decision-making process, this paper describes one of the events namely adoption belief. Adoption belief of young people becomes important because they are potential early adopter on technology-based innovation. How these group of people understands the meaning of having one or more than one gadget would determine the potential adopting decision. Therefore, this paper elaborates adoption belief of a survey on high school student in Surabaya. The result shows that smartphone has received highest adoption belief, followed by tablet and cellular phone.